2004
DOI: 10.1046/j.1600-6143.2003.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Squamous Cell Carcinoma of Donor Origin Treated With Immunosuppression Withdrawal and Liver Retransplantation

Abstract: Posttransplantation allograft malignancy of donor origin is a rare complication after liver transplantation. In the case described, subjective fevers and nonspecific abdominal complaints nearly 6 months following cadaveric liver transplantation in a young woman prompted an evaluation which was remarkable for a large central liver mass. A poorly differentiated squamous cell carcinoma was diagnosed, but was unresectable at exploration. The tumor was confined to the liver. Histocompatibility testing using polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The management of patients diagnosed with donor‐derived malignancy also remains a matter for debate. This case, along with other similar cases,2, 5, 10, 11 gives some evidence that emergency retransplantation in hepatic grafts appears to be curative. The role for radioablation, immunosuppression, and chemotherapy is less clear‐cut.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The management of patients diagnosed with donor‐derived malignancy also remains a matter for debate. This case, along with other similar cases,2, 5, 10, 11 gives some evidence that emergency retransplantation in hepatic grafts appears to be curative. The role for radioablation, immunosuppression, and chemotherapy is less clear‐cut.…”
Section: Discussionsupporting
confidence: 68%
“…In sex‐mismatched allografts, this distinction can be made with chromosomal analysis 5, 6. More recently, microsatellite analysis has allowed the detection of tumor lineage of both donor7, 10–14 and recipient origin 15, 16…”
mentioning
confidence: 99%
“…The patient's good therapeutic response and clinical stability over a period of 6 months suggested that retransplantation should be offered as definitive treatment. We never considered a trial of complete withdrawal of immunosuppression because we believed we had successfully controlled the patient's hepatic disease: a PET/CT scan performed 40 days before retransplantation demonstrated no extrahepatic disease 13…”
Section: Discussionmentioning
confidence: 99%
“…Reducing immunosuppression and switching to a calcineurin inhibitor–free regimen, in addition to radical surgery and/or adjuvant systemic chemotherapy in selected cases, could be justified according to the tumor type and to the patient characteristics. In cases in which the donor cancer was diagnosed several months after transplantation, complete interruption of immunosuppression was proposed to induce cancer rejection 16. This policy, in addition to systemic chemotherapy and retransplantation as the rejection process induces liver graft failure, was successfully reported 16.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which the donor cancer was diagnosed several months after transplantation, complete interruption of immunosuppression was proposed to induce cancer rejection 16. This policy, in addition to systemic chemotherapy and retransplantation as the rejection process induces liver graft failure, was successfully reported 16. However, cases of successful liver retransplantation are rare,17 and the management of liver recipients diagnosed with transplanted malignant tumor remains highly challenging.…”
Section: Discussionmentioning
confidence: 99%